Agricultural Budgetary Allocation and Economic Growth in Nigeria: Implications for Agricultural Transformation in Nigeria - Oyinbo, Oyakhilomen; Zakari, Abdulsalam; Rekwot, Grace Zibah (Consilience, 2013)
This paper was designed to investigate the linkage of Agricultural budgetary allocation and economic growth in Nigeria from an econometric perspective. The results of the analysis showed that in the long run, the relationship between agricultural budgetary allocation and economic growth in Nigeria is positive but not significant and in the short run, the relationship is positive and significant only for two years lagged value of agricultural budgetary allocation. This observed relationship is not unconnected to the low budgetary allocations to agriculture over the years in Nigeria. This implies that there is the need for a significant increase in allocations to agriculture in order to ensure that the agricultural sector plays a pivotal role in the national transformation agenda of Nigeria.